2009
DOI: 10.1186/ar2799
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate alleviates development of collagen II-induced arthritis in female DBA/1 mice

Abstract: IntroductionDichloroacetate (DCA) has been in clinical use for the treatment of lactacidosis and inherited mitochondrial disorders. It has potent anti-tumor effects both in vivo and in vitro, facilitating apoptosis and inhibiting proliferation. The pro-apoptotic and anti-proliferative properties of DCA prompted us to investigate the effects of this compound in arthritis.MethodsIn the present study, we used DCA to treat murine collagen type II (CII)-induced arthritis (CIA), an experimental model of rheumatoid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 41 publications
4
27
0
1
Order By: Relevance
“…Mechanisms that control cell metabolism to support the specific functional needs of these cells have been described only recently (MacIver et al, 2013), but have proven promising (Bian et al, 2009; Eleftheriadis et al, 2013; Ostroukhova et al, 2012; Shi et al, 2011). To date, pharmacologic approaches have provided limited mechanistic insight, and the role of glucose uptake has been uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms that control cell metabolism to support the specific functional needs of these cells have been described only recently (MacIver et al, 2013), but have proven promising (Bian et al, 2009; Eleftheriadis et al, 2013; Ostroukhova et al, 2012; Shi et al, 2011). To date, pharmacologic approaches have provided limited mechanistic insight, and the role of glucose uptake has been uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…DCA has also been shown to reduce proinflammatory cytokine production and promote FoxP3 expression in vitro and in several in vivo inflammatory models (19)(20)(21), although the mechanisms involved have not been established.…”
Section: T Cells Undergo Metabolic Reprogramming Toward a Glycolytic mentioning
confidence: 99%
“…While DCA has been previously shown to suppress inflammation in arthritis, asthma, and alloreactivity (19)(20)(21), the specific effect on the differentiated CD4 + T cell subsets has not been examined in vivo. We therefore tested the ability of DCA to suppress the Th17-mediated inflammatory diseases.…”
Section: Inhibition Of Pdhk In Vivo Differentially Affects Th17 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study it was shown that DCA administration in lupus prone or normal mice enhances serum immunoglobulin levels (29), whereas another study has shown that in lupus prone mice DCA had no effect on the levels of anti-dsDNA IgG (9). On the other hand, in a murine model of collagen type II-induced arthritis, DCA alleviated arthritis only in female mice, in which it decreased anti-collagen type II antibodies without affecting the T cell response (30). In addition, although upon activation murine B-cells exhibit a balanced increase in lactate production and oxygen consumption, the induction of glycolysis is critical for B-cell proliferation and antibody production since DCA abrogated both of these processes (14).…”
Section: Discussionmentioning
confidence: 96%